THE CONCEPT OF HUMAN AND NATURE DESCRIBING GRIEVING STAGES IN MAYA ANGELOU’S “WHEN GREAT TREES FALL” - Arielia Yustisiana (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
The research aimed to discuss the theme of the poem entitled “When Great Trees Fall” written by an African American poet, Maya Angelou. The theme stated implicitly in the poem was stages of grief. Therefore, the objectives of the research discussed: 1) stages of grief in Maya Angelou’s “When Great Trees Fall”, and 2) the concept of human and nature that describes grieving stages in the poem. The stages of grief that were implicitly stated in the poem meet the theory of stages of grief explained by Elizabeth Kübler-Ross. Besides, the theory of symbol was also used to analyze some images that presented some stages of grief experienced by the speaker of the poem. Dealing with the concept of human and nature, the theory of nature and that of ecocriticism met the analysis. Descriptive method was useful in the research, and three approaches were used to support the analysis were psychological, structural and formalist approaches. The research found that there were four stages of grief portrayed in the poem implicitly, that is, isolation, anger, depression and acceptance. While the concept of human and nature in the poem was described the use of natural phenomena and one of natural elements of life, that is, air. Even though the speaker felt grief because of the loss of the loved one, she is able to breathe in order to live the life.